2005
DOI: 10.1007/bf03167492
|View full text |Cite
|
Sign up to set email alerts
|

A functionally fitted three-stage explicit singly diagonally implicit Runge-Kutta method

Abstract: A special class of Runge-Kutta(-Nystrom) methods called functionally fitted (or functional fitting) Runge-Kutta (FRK) methods has recently been proposed by the author. This class of methods is designed to be exact, if the solution of the equation to be solved is an element of the linear space of given functions, which is called the basis functions. The purpose of this article is to develop a functionally fitted Runge-Kutta method that is cheap to implement. The method proposed in this paper is a three-stage ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…The idea of constructing RK methods which integrate exactly a set of linearly independent functions different from the polynomials has been proposed by several authors (see for example [4,[11][12][13]19,21]). This idea consists in selecting the available parameters of the method (5) and (6) in order to be exact for a set of linearly independent functions…”
Section: Basic Notations and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of constructing RK methods which integrate exactly a set of linearly independent functions different from the polynomials has been proposed by several authors (see for example [4,[11][12][13]19,21]). This idea consists in selecting the available parameters of the method (5) and (6) in order to be exact for a set of linearly independent functions…”
Section: Basic Notations and Definitionsmentioning
confidence: 99%
“…Some results on the existence of a unique solutions for the coefficients of an EFRK method are obtained in [11,12], and several authors [3,5,7,11,13,19] have derived methods with variable coefficients that are able to integrate exactly first or second order differential systems whose solutions belong to the linear space generated by the set of functions {1, t, . .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By construction, FRK methods are inherently implicit. But semi-implicit or diagonally-implicit methods can be obtained by imposing a lower triangular pattern to the RK matrix [10].…”
Section: 1mentioning
confidence: 99%
“…(1) exponential fitting which take advantage of the special properties of the solution of (1) that may be known in advance have been proposed (see [4,5,13,13,14,21,[24][25][26]30,33]). It is also shown that the TFBTDM can be used to solve the general second-order IVPs of the form…”
Section: Introductionmentioning
confidence: 99%